Effects of dapagliflozin in DAPA-HF according to background heart failure therapy. (28th March 2020) - Docherty, Kieran F; Jhund, Pardeep S; Inzucchi, Silvio E; Køber, Lars; Kosiborod, Mikhail N; Martinez, Felipe A; Ponikowski, Piotr; DeMets, David L; Sabatine, Marc S; Bengtsson, Olof; Sjöstrand, Mikaela; Langkilde, Anna Maria; et al.
Abstract: Aims: In the DAPA-HF trial, the SGLT2 inhibitor dapagliflozin reduced the risk of worsening heart failure (HF) and death in patients with HF and reduced ejection fraction. We examined whether this benefit was consistent in relation to background HF therapy. Methods and results: In this post hoc analysis, we examined the effect of study treatment in the following yes/no subgroups: diuretic, digoxin, mineralocorticoid receptor antagonist (MRA), sacubitril/valsartan, ivabradine, implanted cardioverter-defibrillating (ICD) device, and cardiac resynchronization therapy. We also examined the effect of study drug according to angiotensin-converting enzyme inhibitor/angiotensin receptor blocker dose, beta-blocker (BB) dose, and MRA (≥50% and <50% of target dose). We analysed the primary composite endpoint of cardiovascular death or a worsening HF event. Most randomized patients ( n  = 4744) were treated with a diuretic (84%), renin–angiotensin system (RAS) blocker (94%), and BB (96%); 52% of those taking a BB and 38% taking a RAS blocker were treated with ≥50% of the recommended dose. Overall, the dapagliflozin vs. placebo hazard ratio (HR) was 0.74 [95% confidence interval (CI) 0.65–0.85] for the primary composite endpoint ( P  < 0.0001). The effect of dapagliflozin was consistent across all subgroups examined: the HR ranged from 0.57 to 0.86 for primary endpoint, with no significant randomized treatment-by-subgroup interaction. For example, the HR in patients taking a RAS blocker, BB, and MRA at baseline was 0.72 (95% CI 0.61–0.86) compared with 0.77 (95% CI 0.63–0.94) in those not on all three of these treatments ( P -interaction 0.64). Conclusion: The benefit of dapagliflozin was consistent regardless of background therapy for HF.